Cabozantinib in combination with immune checkpoint inhibitors for renal cell carcinoma: a systematic review and meta-analysis - Su, Jingyang; Zhang, Jialin; Wu, Yuqian; Ni, Cui; Ding, Yueyue; Cai, Zelin; Xu, Ming; Lai, Mingyang; Wang, Jue; Lin, Shengyou; Lu, Jinhua (Frontiers in Pharmacology, 2024)
Context: Cabozantinib combined with immune checkpoint inhibitors (ICIs) has brought a new therapeutic effect for the medical treatment of renal cell carcinoma (RCC). Objectives: We performed a meta-analysis of randomized controlled trials and single-arm trials to evaluate the efficacy and safety of cabozantinib plus ICIs in RCC. Methods: We extracted data from PubMed, Cochrane, Medline and Embase databases, and rated literature quality through Cochrane risk of bias tool and MINORS. RevMan5.3 software was used to analyze the results of randomized controlled trials and single-arm trials. Results: A total of 7 studies were included. Treatment with cabozantinib plus ICIs improved PFS [HR 0.75, (95%CI: 0.52, 1.08), P=0.12] and the OS [HR 0.80, (95%CI: 0.60, 1.07), P=0.13] in randomized controlled trials. Meanwhile, the result of the ORR in randomized controlled trials was [risk ratio (RR) 1.37, (95%CI: 1.21, 1.54), P<0.00001] and in single-arm trials was [risk difference (RD) 0.49, (95%CI: 0.26, 0.71), P<0.0001]. Conclusion: Cabozantinib plus ICIs prolonged the PFS and OS, and improved ORR in patients with RCC. Our recommendation is to use cabozantinib plus ICIs to treat advanced RCC, and to continuous monitor and manage the drug-related adverse events.